The Effect of Winter Length on Duration of Dormancy and Survival of Rhagoletis completa (Diptera: Tephritidae) and Associated Parasitoids From Northeastern Mexico. Issue 3 (16th May 2019) - Rull, Juan; Lasa, Rodrigo; Guillén, Larissa; Aluja, Martin
Abstract: The walnut husk fly Rhagoletis completa (Cresson), native to the Midwestern United States and Mexico, is invasive in California and Europe. It is one of the most important pests of walnuts in areas gathering 30% of the world production. Knowledge of life-history regulation is important for the design of management strategies. Research on dormancy has been performed on invasive populations, and not on populations at the southern extreme of its native range. Here, we examined the effect of winter length on fly and parasitoid emergence, survival, and duration of dormancy. Percent emergence was higher for chill periods at 5°C ranging from 8 to 20 wk. No or insufficient chill resulted in low emergence and a significant proportion of individuals in prolonged dormancy (>1 yr). Duration of dormancy was longer for pupae at constant temperatures and a 4-wk chill period than longer winter durations. Dormancy was longer for Mexican than that reported for U.S. populations, suggesting the existence of a latitudinal cline where populations at southern latitudes have evolved slower metabolic rates. Three parasitoid species were found associated with R. completa ( Aganaspis alujai (Wharton and Ovruski) (Hymenoptera: Figitidae), Diachasmimorpha juglandis Muesebeck, and Diachasmimorpha mellea Gahan) (Hymenoptera: Braconidae). Results suggest that rearing of R. completa is possible by subjecting pupae to chill periods between 8 and 20 wk. Overwintering mortality of flies and A. alujai could be further reduced above 5°C. Our findings can contribute for the accurate development of predictive models on invasion potential, development, fly and parasitoid rearing, and biological control.